Gambaran Manajemen Alat Pelindung Diri (APD) Radiasi di Instalasi Radiologi Rumah Sakit Bhayangkara Palembang - Tassya Damayanti; Mustika Fatimah; Rizka Muliani; Anisah Anisah; Hasto Pratikno; Muthia Feliyanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The radiology installation is one of the supporting specialist medical services at the hospital that uses x-rays for diagnosis. One of the efforts to protect workers from occupational health and safety in radiology installations is to implement a radiation Personal Protective Equipment (PPE) management system. This type of research is descriptive qualitative with observation data collection techniques, interviews with two informants and documentation studies. Test the validity of the data using source triangulation techniques and triangulation techniques. This study shows that from 4 variables, 18 components, 27 points where as many as 14 points (51.85%) are met and in accordance with standards, 1 point (3.70%) is met but not according to standards/regulations, and as many as 12 points (44.44%) are not met by the radiology installation of Bhayangkara Hospital Palembang. Several radiation protection requirements and Standard Operating Procedures (SOP) for the operation of radiology equipment and the use of Personal Protective Equipment (PPE) at the radiology installation of Bhayangkara Hospital Palembang have met the standards and related education and training have been carried out.